1995
DOI: 10.1079/bjn19950087
|View full text |Cite
|
Sign up to set email alerts
|

The importance of dietary polyamines in cell regeneration and growth

Abstract: The polyamines putrescine, spermidine and spermine are essential for cell renewal and, therefore, are needed to keep the body healthy. It was previously believed that polyamines are synthesized by every cell in the body when required. However, in the present paper evidence is provided to show that, as in the case of the essential amino acids, the diet can supply sufficient amounts of polyamines to support cell renewal and growth. Systematic analysis of different foods was carried out and from the data obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
148
2
6

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(169 citation statements)
references
References 21 publications
7
148
2
6
Order By: Relevance
“…The levels of the other polyamines (spermidine and putrescine) and of N-acetylspermidine and N-acetylspermine were not modified. These results indicate that no important interconversion occurred from spermine to spermidine and to putrescine ; they agree with those of Bardocz et al [18], which showed that polyamines are readily taken up from the lumen and that spermine is not as strongly metabolized as putrescine. In suckling rats treated orally with spermine, the increase in the intestinal content of spermine in comparison with control rats is probably due to the intake, at the apical pole of the epithelial cells, of a higher quantity of this polyamine that is present in the gut lumen, rather than to a higher contribution via blood circulation, because intraperitoneal administration of spermine was without effect.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The levels of the other polyamines (spermidine and putrescine) and of N-acetylspermidine and N-acetylspermine were not modified. These results indicate that no important interconversion occurred from spermine to spermidine and to putrescine ; they agree with those of Bardocz et al [18], which showed that polyamines are readily taken up from the lumen and that spermine is not as strongly metabolized as putrescine. In suckling rats treated orally with spermine, the increase in the intestinal content of spermine in comparison with control rats is probably due to the intake, at the apical pole of the epithelial cells, of a higher quantity of this polyamine that is present in the gut lumen, rather than to a higher contribution via blood circulation, because intraperitoneal administration of spermine was without effect.…”
Section: Discussionsupporting
confidence: 92%
“…It could be interesting to determine the nature of one of them (with a molecular mass of 100 kDa), which was more strongly revealed than the others and might be one of the glycoprotein enzymes of the brush border membrane (e.g. sucrase, maltase or aminopeptidase), also precociously induced after spermine ingestion [18,36]. However, it remains to be determined whether the precocious induction of intestinal fucosylation, observed in suckling rats treated orally with spermine, is due to a direct effect of polyamines after enterocyte penetration at the luminal side of the cell or to an indirect stimulated secretion of hormone or of other secondary effectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, although urea-cycle enzymes are expressed primarily in the liver and intestine, polyamines are made in all tissues. Polyamines are also obtained from the diet (foods that are high in polyamines include cheese and red meat 3 ) and from other sources, such as intestinal bacteria 1,4 . These externally derived polyamines are transported into cells from extracellular spaces.…”
mentioning
confidence: 99%
“…This chemical affects numerous biological processes, including cell growth and proliferation, tissue regeneration, DNA and RNA stabilization, enzymatic modulation, and regulation of translation, among others [13]. Furthermore, spermidine exhibits anti-inflammatory and antioxidant properties, enhances mitochondrial metabolic function and respiration, promotes chaperone activity and improves proteostasis [4].…”
mentioning
confidence: 99%